(untitled) (Plant Tissue Culture and Biotechnology, 2009)
A suitable callus induction and efficient regeneration protocol for orchardgrass (Dactylis golomerata L.) was developed. It consisted of 3 mg/l 2,4-D + 0.1 mg/l BA + 1 g/l CH + 300 mg/l L-proline + 40 mg/l L-cysteine + 30 g/l sucrose in MS showed the highest percentage of callus induction. Maltose exhibited better in regeneration than other types of carbon sources. Highest (71%) regeneration was obtained from N6 medium containing 1 mg/l 2,4-D + 3 mg/l BA + 1 g/l CH + 300 mg/l L-proline + 40 mg/l L-cysteine + 30 g/l maltose. Among the nine cultivars of orchardgrass (Dactylis golomerata L.), genotypic variation was observed in both callus induction and regeneration. Overall callus induction and regeneration rates were 23 - 73 and 17 - 71%, respectively. Key words: Dactylis golomerata, Orchardgrass, Mature seeds, Additives, Regeneration, Maltose. D.O.I. 10.3329/ptcb.v17i2.3240 Plant Tissue Cult. & Biotech. 17(2): 193-207, 2007 (December)